2023
DOI: 10.1002/jgc4.1705
|View full text |Cite
|
Sign up to set email alerts
|

Advancing health equity: A qualitative study assessing barriers and facilitators of implementing hereditary breast and ovarian cancer risk screening tools in community‐based organizations

Abstract: Genetic counseling and testing (GCT) inform cancer management for persons at risk for hereditary breast and ovarian cancer (HBOC). Community‐based organizations (CBOs) may play a role in identifying at‐risk Latinx individuals to connect them to GCT but data are lacking. Two academic centers and their four CBO partners planned to implement a validated questionnaire for HBOC risk screening (“HBOC risk screening tool”). This study aimed to assess CBO's preferences for HBOC risk screening tools, as well as the bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Other barriers to testing have been described in the literature including access, insurance issues, other socioeconomic characteristics, patient risk perception, psychological well‐being and knowledge about/understanding of genetic testing, and primary care physician discussion of BRCA1/2 testing. It has been demonstrated that racial and ethnic minorities less frequently undergo genetic testing (Armstrong, 2005; Bowen et al, 2023; Chapman‐Davis et al, 2021; Hanson et al, 2023; Hong et al, 2023; Jones et al, 2017; Kurian et al, 2019, 2021). The current report is based on a consecutive population of patients seen as outpatients for ovarian cancer, but notably, the study population does lack diversity and reflects the general underrepresentation of minorities in clinical studies focusing on genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers to testing have been described in the literature including access, insurance issues, other socioeconomic characteristics, patient risk perception, psychological well‐being and knowledge about/understanding of genetic testing, and primary care physician discussion of BRCA1/2 testing. It has been demonstrated that racial and ethnic minorities less frequently undergo genetic testing (Armstrong, 2005; Bowen et al, 2023; Chapman‐Davis et al, 2021; Hanson et al, 2023; Hong et al, 2023; Jones et al, 2017; Kurian et al, 2019, 2021). The current report is based on a consecutive population of patients seen as outpatients for ovarian cancer, but notably, the study population does lack diversity and reflects the general underrepresentation of minorities in clinical studies focusing on genetics.…”
Section: Discussionmentioning
confidence: 99%